Waters Above, Waters Below: Conceptions of the Water Cycle in Abbasid-Era Thought - Borroni, Massimiliano (Journal of Abbasid Studies, 2025)
This article investigates philosophical and scientific thinkers’ conceptions of the water cycle during the Abbasid period. It focuses on authors who disregarded or negated the subterranean generation of water envisaged in Aristotelian doctrines, which form the mainstream of Arabo-Islamic natural philosophy. The historical authors analysed are Thābit b. Qurra, Abū l-Barakāt al-Baghdādī, Ikhwān al-Ṣafāʾ, al-Bīrūnī, Miskawayh, and al-Karajī. Their diverse conceptions reveal the central role of Thābit b. Qurra and possible accommodations between endogenous and exogenous conception of the water cycle. This investigation sheds light on the historical evolution of the understanding of the water cycle and may contribute to contemporary discussions and advancements in hydrology.